Studi Literatur Kritis Risiko Reputasi pada Manajemen Risiko Perbankan Syariah - Afrizal; Saparuddin Siregar; Sugianto (Jurnal EMT KITA, 2022)
Reputation is the most important intangible asset owned by a bank. Reputation reflects the success of the bank in meeting the expectations of various stakeholders. Creating reputation is a key element of organizational strategy, especially banking. Any important issues related to the operations of Islamic banks, whether in terms of non-compliance with Sharia financial products or customer complaints, can damage the reputation of Sharia banks. This study aims to analyze the determinants of reputation risk and its impact on Islamic banking and how to implement reputation risk management in Islamic banking. This study uses a literature study approach to answer the research objectives, while the analytical technique used in this study is content analysis. Thus, Islamic banks are expected to pay more attention to reputation risk management.